Strategi Pengelolaan Pariwisata di Masa Pandemi Covid-19 (Studi di Wisata Kawung Tilu Kabupaten Bekasi) - Puziah, Dini Septi; Argenti, Gili; Marsingga, Prilla (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
The Covid-19 pandemic has resulted in global and local tourism slumping, which is influenced by the implementation of social restrictions and even the closure of tourist attractions, causing the level of tourist visits has been decreased drastically. That problem is a challenge for the government to seek strategic steps in accelerating its recovery with the intention that the tourism sector continues to develop and be able to carry out activities by implementing health protocols during the Covid-19 pandemic. One of the tourist attractions in the Bekasi Regency that has been affected by the Covid-19 pandemic is the Wisata Kawung Tilu. This research was conducted since one of the locations vulnerable to the spread of the Covid-19 virus is a tourist spot. The purpose of this study was to describe how the Wisata Kawung Tilu management strategies in Bekasi Regency were during the Covid-19 pandemic. The focus of this study used the variable theory of strategy, according to J. Winardi (2003), which consists of goals, policies, and stages. This study used a descriptive study method with a qualitative approach. The study results indicated that the Wisata Kawung Tilu management strategies emphasize the management of providing facilities and infrastructure that meet health protocols as well as visitor management. Management has been considered to be quite good by promoting in online media, conducting collaboration between the Bekasi Regency Tourism Department and the National Task Force for Covid-19 Handling in the form of observing tourism-sites as well as Kawung Tilu Tourism entrepreneurs with the Kelompok Sadar Wisata (Tourism Awareness Group) of Kawung Tilu. The Wisata Kawung Tilu has implemented facilities that support health protocols such as portable sinks, body temperature thermometers, hand sanitizers, and masks. The Covid-19 pandemic has resulted in global and local tourism slumping, which is influenced by the implementation of social restrictions and even the closure of tourist attractions, causing the level of tourist visits has been decreased drastically. That problem is a challenge for the government to seek strategic steps in accelerating its recovery with the intention that the tourism sector continues to develop and be able to carry out activities by implementing health protocols during the Covid-19 pandemic. One of the tourist attractions in the Bekasi Regency that has been affected by the Covid-19 pandemic is the Wisata Kawung Tilu. This research was conducted since one of the locations vulnerable to the spread of the Covid-19 virus is a tourist spot. The purpose of this study was to describe how the Wisata Kawung Tilu management strategies in Bekasi Regency were during the Covid-19 pandemic. The focus of this study used the variable theory of strategy, according to J. Winardi (2003), which consists of goals, policies, and stages. This study used a descriptive study method with a qualitative approach. The study results indicated that the Wisata Kawung Tilu management strategies emphasize the management of providing facilities and infrastructure that meet health protocols as well as visitor management. Management has been considered to be quite good by promoting in online media, conducting collaboration between the Bekasi Regency Tourism Department and the National Task Force for Covid-19 Handling in the form of observing tourism-sites as well as Kawung Tilu Tourism entrepreneurs with the Kelompok Sadar Wisata (Tourism Awareness Group) of Kawung Tilu. The Wisata Kawung Tilu has implemented facilities that support health protocols such as portable sinks, body temperature thermometers, hand sanitizers, and masks.